(untitled) (World Bulletin of Management and Law, 2024)
The article examines the critical importance of procedural fairness and the preservation of defendants’ rights in competition law enforcement, based on examples from both the European Union (EU) and Uzbekistan. It refers to the recent OECD Recommendation on Transparency and Procedural Fairness in Competition Law Enforcement, as well as Article 47 of the EU Charter of Fundamental Rights, which emphasises the concepts of openness, independence, and the right to defence. Administrative processes in Uzbekistan describe procedural fairness principles, with a particular emphasis on the ability to be heard and participate in proceedings. The study finishes with a comparative analysis, emphasising the similar dedication to due process and protecting rights in competition procedures in both nations, but also highlighting contrasts in approaches to confidentiality and business secrecy.